2012
DOI: 10.1080/01443410.2012.730479
|View full text |Cite
|
Sign up to set email alerts
|

Studying for the sake of others: the role of social goals on academic engagement

Abstract: Much of the research on achievement goal theory has focused on the roles of mastery and performance goals in academic engagement, thus the role of other goals such as social goals has mostly been neglected. The aim of this research was to investigate the effects of different kinds of social goals (affiliation, approval, concern, responsibility and status goals) on the different facets of academic engagement. A total of 1147 Filipino secondary school students answered questionnaires assessing their social goals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 103 publications
(115 reference statements)
2
38
0
1
Order By: Relevance
“…When the two models were examined together in the same regression model (see Model 3 in Table 1), the two models only explained 11% of variance in students' academic achievement. Future research may examine other important variables within the Omani school context such as students' self-efficacy beliefs (Aldhafri, 2016) and social goals (King, McInerney, & Watkins, 2012 as self-related variables or classroom climate and students' perceptions of parenting styles as context-related variables.…”
Section: Discussionmentioning
confidence: 99%
“…When the two models were examined together in the same regression model (see Model 3 in Table 1), the two models only explained 11% of variance in students' academic achievement. Future research may examine other important variables within the Omani school context such as students' self-efficacy beliefs (Aldhafri, 2016) and social goals (King, McInerney, & Watkins, 2012 as self-related variables or classroom climate and students' perceptions of parenting styles as context-related variables.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, these orientations may directly influence students' psychological processes as they strive toward academic achievement." Numerous studies have shown how social goals are linked to academic outcomes although the studies done are much fewer when compared to those on mastery and performance goals (e.g., Dowson & McInerney, 2001King, McInerney, & Watkins, 2012bMiller, Greene, Montalvo, Ravindran, & Nichols, 1996;Ryan, Hicks, & Midgley, 1997).…”
Section: Personal Investment Theorymentioning
confidence: 99%
“…Achievement goal theory has been criticized of being based on an individualistic interpretation of achievement strivings. Some cross-cultural researchers argue that in collectivist settings, there is a need to focus on more socially oriented types of goals (Dowson & McInerney, 2001King, McInerney, & Watkins, 2012bTao, 2003;Urdan & Maehr, 1995;Yang & Yu, 1994). As such, achievement goal theory has been criticized because of its exclusive focus on individualistic types of goals.…”
Section: Achievement Goal Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that the Filipino and English versions of psycho-educational instruments function equivalently in the Philippine context (e.g., Bernardo, Lising, & Shulruf, 2012;Ganotice, Bernardo, & King, 2012. Moreover, many studies conducted in the Philippines have also relied exclusively on English versions of questionnaires and found them to be adequate (e.g., Bernardo, Zhang, & Callueng, 2002;King, McInerney, & Watkins, 2012;King & Watkins, 2011;Watkins, Hattie, & Astilla, 1986).…”
Section: Motivational Interferencementioning
confidence: 99%